Assessing the Influence of Strategic Management Strategies on Organizational Performance in Rwanda’s Private Construction Firms (International Journal of Scientific Research and Management (IJSRM), 2024)
This study was carried out to examine the influence of strategic management strategies on organizational performance in Rwanda’s private construction firms. This based on a number of issues that were found to face construction projects that are private in Rwanda in relation to their performance and the major challenge was strategic management. The study was guided by the following specific objectives: to examine the effect of strategic planning and resource allocation on project efficiency and profitability among the private construction firms in Rwanda; to establish the role of innovation and technology adoption in enhancing operational performance in the Rwanda’s private construction sector; to find out the impact of leadership and strategic decision-making practices on the competitive positioning and market share growth among private construction firms in Rwanda. The study was guided by the Resource Based View (RBV) theory, which is a key foundational theoretical framework in strategic management that provides an insight into how organizations internal resources can be used as valuable sources for developing competitive advantages and achieving higher performance. In the current study, a mixed-methods research was adopted incorporating the descriptive research design. Due to the nature of the research and the intendent purpose of the study, a population census was carried out to give equal representation of these firms. Therefore, the sample size used was the 150 respondents. Census is the process of collecting data from every member of a population, and census data is more accurate and precise than sampling data, as it includes information from every member of the population; a reason as to why it was considered for this study. Primary data was collected by use of structured questionnaires and semi-structured interviews with the questionnaire being Likert scale rated in order to collect the quantitative data while semi-structured interviews were used to collect the qualitative data. The results did find that from a regression analysis, all three strategic management practices—strategic planning and resource allocation, innovation and technology adoption, and leadership and strategic decision-making—were statistically significant predictors of organizational performance, with p-values less than 0.01. Innovation and technology adoption has the highest standardized coefficient (β = 0.39), indicating that it has the strongest impact on organizational performance. Leadership and strategic decision-making (β = 0.35) and strategic planning and resource allocation (β = 0.32) also have significant positive effects, though to a slightly lesser extent. The model’s R² value of 0.62 suggests that these strategic management practices collectively explain 62% of the variance in organizational performance, a substantial impact. The study recommended that an integrated management approach be adopted by private construction companies in Rwanda. Step one: Allocate time and resources to strategic planning and planning for project time, cost and resource utilization. Also, the assimilation and innovation of technology should be promoted as technological advancements in construction and project management speculation have been shown to increase productivity and decrease costs. Companies spend money on training programs at all levels in technology and skills. Moreover, development of leadership and decision-making skills are vital as well and companies must design leadership development programs that ensure managers are swift and well-informed in making consequential decisions that are in line with organizational objectives and market movements. Policymakers and industry partners are also encouraged to support this by creating policies that provide tax incentives or subsidies to support technology adoption, innovation and education for construction workers. Using these concepts, the construction industry in Rwanda can better respond to competition, contribute to the country’s development and economic goals, and maintain a stable position in the growing market in East Africa.